Extra-articular manifestations of rheumatoid arthritis: risk factors for serious gastrointestinal events. - Voskuyl, A E (1993)
OBJECTIVES--Serious upper gastrointestinal events are an important threat to patients with arthritis who are treated with non-steroidal anti-inflammatory drugs (NSAIDs). In this study risk factors for serious upper gastrointestinal events are identified in patients with possible or definite rheumatoid arthritis (RA). METHODS--A retrospective analysis of factors that might contribute to the risk of serious upper gastrointestinal events was performed in a cohort of 2315 consecutive patients with possible or definite RA. The relative influences of disease severity, drug treatment, particularly with corticosteroids, and history of peptic ulceration were analysed with a conditional logistic regression model for the 106 patients with serious upper gastrointestinal intestinal events and for an equal number of control patients who were matched for age, gender, number of criteria for RA, and disease duration. RESULTS--The incidence rate for serious upper gastrointestinal events was 4.0/1000 patients in each year. The study reconfirmed that age over 60 years, history of peptic ulceration, and use of corticosteroids are risk factors. The presence of extra-articular manifestations of RA was associated with a two to 11-fold increase in the risk for serious upper gastrointestinal events. This risk was independent of the use of corticosteroids. CONCLUSION--Disease severity, in particular the presence of extra-articular features, may be an important factor in the pathogenesis of upper gastrointestinal ulceration in patients with RA who are treated with NSAIDs.